(3QSGdI aj HjGf GdCQcGfs ((3CjhH Hf YKeGf s)
(3ChdgG (B:s
(3GdaUd GdaUd GdChd ai GdfGQ hajg KdGKI eHGMK GdHMK GdChd ai EKHGJ cQI GdfGQ GdLSe GdbGHd ddSNhfI ehLH dSNhfJg s
(3BNQgG (B:s
(3adGjecf Cf jMUd NGQL GdYGde cQI CNQi aGdYGde hGMO s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdLZQGajG h GdHdOGfs